2015
DOI: 10.18801/jbar.040215.43
|View full text |Cite
|
Sign up to set email alerts
|

Reduction of arsenic entry into rice from arsenic contaminated soil using Pteris vittata as trap plant

Abstract: An experiment was conducted to reduce the entrance of arsenic on rice plant. Experiment consisted three different density of the trap plants viz. P1: No P. vittata (control); P2: four P. vittata plant per m 2 and P3: eight P. vittata plant per m 2. Inter planting of four P. vittata per m 2 reduced 96.24 % and eight P. vittata per m 2 reduced 97.01% arsenic accumulation into rice. Maximum yield was found from P2 (34.2 g per plant) which was statistically similar with P3 (32.9 g per plant) while minimum was foun… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(6 citation statements)
references
References 17 publications
0
6
0
Order By: Relevance
“…due to the As-contaminated irrigation water (Santra et al, 2013). Highest arsenic accumulation in tuber peel was found from P0 (5.46 ppm) and lowest from P4 and P8 (0.44 ppm and 0.41 ppm respectively) whereas P4 and P8 were found to be statistically identical ( (Mayda et al, 2015). Hyperaccumulators are plants that can take up and concentrate greater than 0.1% of a given element in their tissue.…”
Section: Arsenic Accumulationmentioning
confidence: 99%
See 2 more Smart Citations
“…due to the As-contaminated irrigation water (Santra et al, 2013). Highest arsenic accumulation in tuber peel was found from P0 (5.46 ppm) and lowest from P4 and P8 (0.44 ppm and 0.41 ppm respectively) whereas P4 and P8 were found to be statistically identical ( (Mayda et al, 2015). Hyperaccumulators are plants that can take up and concentrate greater than 0.1% of a given element in their tissue.…”
Section: Arsenic Accumulationmentioning
confidence: 99%
“…Arsenic is toxic to most plants at higher concentration (Marin et al, 1993) and inter-planting of P. vittata caused better plant growth by reducing soil arsenic toxicity for rice (Mayda et al, 2015). It interfered with metabolic processes and inhibited plant growth and development through arsenic induced phytotoxicity.…”
Section: Plant Height and Leaves Numbermentioning
confidence: 99%
See 1 more Smart Citation
“…Phytoremediation and PGPB (Plant Growth Promoting Bacteria) remediation are some of the methods used under bioremediation for mitigation of As toxicity (Rojas-Solis et al, 2023). Mayda et al (2014) conducted an experiment from October 2012 to April 2013 in the Department of Botany, Jahangirnagar University, Dhaka, Bangladesh. They studied the process in four non-edible ferns and four soil As concentrations.…”
Section: Phytoremediationmentioning
confidence: 99%
“…They studied the process in four non-edible ferns and four soil As concentrations. Using non edible plant material for mitigating As, they showed that these plants help by stopping As toxicity from entering the food chain (Mayda et al, 2014). Out of the four ferns observed, Pteris vittate L. was found as the As hyperaccumulating plant.…”
Section: Phytoremediationmentioning
confidence: 99%